Theoretical studies on triaryamine‐based p‐type D‐D‐π‐A sensitizer. Issue 10 (18th February 2019) - Kong, Li‐Xiao; He, Mingfei; Yan, Wen; Zhang, Chang‐Shan; Ju, Xue‐Hai
Abstract : Development of triaryamine‐based nonmetallic dye sensitizers is a hot topic in the solar cell research. A series of triaryamine‐based dyesWS1 –WS7 were designed withW1 as the prototype. Density functional theory (DFT) and time‐dependent‐DFT calculations were used to investigate the effects of the attached donorD on the absorption spectra and electronic properties of the dyes. The light‐harvesting efficiency (LHE), hole injection force (Δ G inj ), dye regeneration force (Δ G reg ), and charge recombination force (Δ G CR ) for all the dyes were predicted. The insertion ofD not only results in a red shift in the absorption spectra for all dyes but also achieves a broader absorption for visible light. Compared with that of the prototype, the absorption peak of the dyeWS7 has a red shift of 95 nm and an oscillator strength increase of 29%. The absorption peak ofWS7 is wider and stronger, and the absorption range extends to 900 nm. The LHE and Δ G reg values ofWS7 are 0.991 and −1.49 eV, respectively. On overall evaluation, WS7 is a promising candidate of a p‐type dye sensitizer with good light absorption and dye regeneration efficiency. Abstract : By inserting donors into the prototypeW1, the absorption peaks are red‐shifted by up to 76 nm.WS7 not only has an obvious red shift and a large overlap with visible light but also has a strong oscillator strength, indicating that the donor dithieno[3, 2‐b:2′, 3′‐d]thiophene (s‐DTT) is beneficial for light harvesting.